Study on the hypolipidemic properties of garlic polysaccharide in vitro and in normal mice as well as its dyslipidemia amelioration in type2 diabetes mice. (June 2022) - Xie, Chanyuan; Gao, Wei; Li, Xue; Luo, Shuangshuang; Chye, Fook Yee
Abstract: In the present work, garlic polysaccharide (GP) in lowering lipid based on in vitro and in vivo approaches were investigated. The in vitro studies revealed significant effects of GP on cholesterol, sodium cholate, oil binding, and lipase inhibition. Meanwhile, the liver index in the medium and high dose GP group was significantly lower than the control group in normal mice which relatively corresponded to the modulated effect of intestinal flora. A high dose of GP has markedly reduced the ratio of intestinal Firmicutes to Bacteroidetes and increased the abundance of gut probiotics Akkermansia . Furthermore, the high dose of GP also significantly reduced the levels of triglyceride and low-density lipoprotein cholesterol of diabetic mice indicating that GP could not only prevent hyperlipidemia of metabolic syndrome but also further ameliorate dyslipidemia of diabetes mellitus. This study provides new prospects for garlic polysaccharide as a hypolipidemic nutraceutical for the treatment of metabolic syndrome and type 2 diabetes. Graphical abstract: Image 1 Highlights: Garlic polysaccharide presented good lipid adsorption function. Garlic polysaccharide significantly enhanced the abundance of Akkermansia. Garlic polysaccharide showed potential prebiotic activities. Garlic polysaccharide showed significant hypolipidemic effect in vivo. Garlic polysaccharide could be served as a promising functional food ingredient.